POLITIK HUKUM PEMBATASAN USIA CALON KEPALA DAERAH BERDASARKAN PASAL 7 AYAT 2 E UNDANG-UNDANG NOMOR 10 TAHUN 2016 TENTANG PERUBAHAN KEDUA ATAS UNDANG- UNDANG NO 1 TAHUN 2015 TENTANG PENETAPAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NOMOR 1 TAHUN 2014 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA MENJADI UNDANG-UNDANG - Yosua Manurung; Mexsasai Indra; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Political rights in relation to the preservation of state life, in article 7 paragraph 2 E Law, Number. 10 '' The year 2016 reads that every person who wants to nominate a regional head must be at least 30 (thirty) years old for the candidate for Governor and candidate for Deputy Governor, 25 (twenty five) Years for the candidate for Regent and candidate for Deputy Regent as well as for the candidate for Mayor and candidate for Deputy Mayor ''. There is a related gap in article 7 paragraph (2) huru e of the Law on Regional Head Elections which contradicts Article 28 J of the 1945 Constitution which contains restrictions on the rights of citizens, but with the intention of guaranteeing recognition and respect for the rights and freedoms of others and fulfilling demands that are just, according to considerations of moral, religious values, security and public order in a democratic society.This type of research is normative research. namely research conducted by means of library materials or secondary materials. In this case the researcher conducts normative legal research which discusses legal principles, in the form of an effort to discover basic philosophical principles. In this case, the researcher discusses the political age limit in the candidacy of regional heads based on statutory regulations. This research is conducted by examining secondary materials or research based on standard rules that have been recorded, also known as literature studies.In the results of the research, there are two points that can be concluded. First, the Legal Politics of determining the Age Limit for candidates for Regional Head in Law No. 10 of 2016 that in order to become a regional head, a person is required to meet the requirements including the minimum age limit to become a regional head, which basically means that the elected regional head will have knowledge and ability as regional leaders able to think and act and behave by prioritizing the interests of the nation, state and society. Second. for someone to serve as a public official, a leader is needed who has intellectual, high social sense, politeness, innovative, creative, and able to make the right decisions wisely to solve a problem that occurs. in this case the authors argue that at the age of 21 years.Keywords: Legal Politics - Age Limitation - Regional Head Candidates